Variations in Fruit and Seed Characteristics and Germination of Tetrapleura Tetraptera (Schum & Thonn.) Taub. From Different Sources in South - Western Nigeria. (1999)
"An assessment was carried out of variability in fruit and seed characteristics and the effects of seed source and seed size on germination of Tetrapleura tetraptera from four sources in South-Western Nigeria. The sources were Emure-Ekiti (Lat. 7°26’N and Long. 5°30’E); Ikoyi-Ue (Lat. 8°15’N and Long. 4°49’E); Osogbo (Lat. 7° 46’ and Long 4°35’E) and Sapele (Lat. 5°55’N and Long. 5°46’E). Fruit length and diameter were determined using a string and a metre-ruler, while fruit and seed weights were measured with an electronic balance and the number of seeds per pod was counted. Seeds were categorised into two, based on sources and size classes for germination studies. Seed dormancy was broken using concentrated Tetra-oxo-sulphate VI acid. The seeds were thoroughly washed in distilled water before sowing in germination boxes filled with top soil.Significant variations were observed both in fruit and seed characteristics and in germination. Mean pod length ranged from 21,60cm to 24.39cm with coefficient of variation of 5.90%. Pod diameter ranged from 3.95cm to 7.5cm with 6.9% coefficient of variation. Mean pod weight ranged from 34.94g to 57.46g with coefficient of variation of 11.11%. The number of seeds per pod varied between 10.46 and 14.04 with coefficient of variation of 14.92%. Seed length varied between 9.12 and 9.78mm with coefficient of variation of 2.58%, while seed diameter and seed weight ranged from 6.26mm to 7.00mm and 1.50g to 1.76g respectively. The coefficient of variation for seed diameter was 7.05% while that of seed weight was 6.91%. Germination pattern also varied according to seed size classes and sources. The largest size class (10.7mm+) gave the highest cummulative germination percentage of 88.2% and a germination rate of 12.52 seeds per day. The size class 6.0 - 7.5mm gave the lowest cummulative germination percentage of 57.5% and a germination rate of 8.19 seeds per day. Seeds from Ikoyi-Ile had a total germination percentage of 92.8% and a germination rate of 12 seeds per day. The lowest total germination of 56.6% was recorded for Osogbo. Interaction effects between mother trees and seed source were significant. There was, however, no significant interaction between seed size and seed source"